Comparative discussion on apprenticeships before and during the COVID-19 pandemic - Shepard, Roger B. [Verfasser]; Zhao, Li [Verfasser]; Denison, Randall [Verfasser] (My University, 2022)
"The COVID-19 pandemic has resulted in significantly increased U.S. Department of Labor (USDOL) com munication with apprenticeship sponsors, educational entities, and wider stakeholder groups. Appren ticeship programs adapted quickly to the pandemic by using web-based tools to provide online-related instruction and distance learning, which has now greatly expanded in response to the COVID-19 pan demic. Throughout the pandemic, schools and training centres focused on the conditions at hand, how to open safely with new protocols, and how to comply with pandemic-related mandates. The situation remains fluid in the U.S. regarding ongoing fears of resurgence, new COVID-19 cases, and shifting pro tocols for education and training institutions in line with the state and local conditions and subsequent regulations." (Author's abstract ; BIBB-Doku)
Keywords: I 2.3.2 Nordamerika; L 4.2.3 Internetbasiertes Lernen / E-Learning; 370; Berufsausbildung; Pandemie; USA; Fernunterricht; E-Learning